SAMAMBAIAS E LICÓFITAS DO PARQUE NACIONAL DA CHAPADA DAS MESAS E ARREDORES, ESTADO DO MARANHÃO, BRASIL - SILVA, Laryssa Reis (2022)
Protected Areas (PAs) are extremely important for the biodiversity conservation worldwide, in addition to beand important research areas that support a large number of studies. This work aimed to carry out a floristic inventory on ferns and lychophyes conductedin the Chapada das Mesas National Park (PNCM), an important PA created in 2005, located in southern portion of the State of Maranhão, an area with a typical Cerrado phytophysiognomy, including riparian forest, springs, streams and waterfalls., These environments are favorable for fern and lycophyte species.. Studies referring to the aforementioned group are still scarce and there are subsampled areas in the state that deserve more attention. As a result of this work, a total of 86 species of ferns and lycophytes were recorded for PNCM, with 21 new records for the State of Maranhão and 11 for the Brazilian Cerrado, representing 94% of the total number of species of ferns and lycophytes known for Maranhão. Moreover, these new records for the state, Cerrado domain and Northeast region corroborate the need to carry out more studies in these biological protected areas that are constantly threatened by human activities.